What is Information? A multidimensional concern - José María Díaz Nafría (tripleC: Communication, Capitalism & Critique, 2010)
Looking for an answer to the posed question, we will first go through a brief historical enquiry aiming at exploring the development of the uses given to the Latin word “information” from its Greek roots until its scientific formalisation in hands of the Mathematical Theory of Communication. Secondly and starting from the conceptual limitations of Shannon’s theory, we will put forward the most important theoretical demands claimed by many scientific and technical fields, directly concerned with the usage of information concepts. Such claims eventually entail an open critic to Shannon’s definition with different degrees of radicality, proposing a perspective change in which the different uses and disciplinary interests might be better represented. In order to foster an interdisciplinary approach aiming at gathering together the competing views of information and at bridging their theoretical and practical interests, a sketched glossary of concepts concerning information is proposed as an interdisciplinary tool.